Cultural Clash: Investigating How Entrepreneural Characteristics and Culture Diffusion affect International Interns’ Competency - Ligia, Emila; Iskandar, Kurniawaty; Surajaya, I Ketut; Bayasut, Mahir; Jayanagara, Oscar; Mizuno, Kosuke (Pandawan, 2024)
The world today is highly interconnected. To address the manpower shortage in Japan and the surplus in Indonesia 30 years ago, both countries developed an internship program,